Utilization of a Model Cocoa Fermentation System and Roasting to Assess Differences Among Bioactive Compounds and Bioactivity of Cocoa Through Variable Processing Conditions (FS07-04-19). (13th June 2019) - Racine, Kathryn; Wiersema, Brian; Lee, Andrew; Griffin, Laura; Essenmacher, Lauren; Moore, Amy; Lambert, Joshua; Stewart, Amanda; Neilson, Andrew
Abstract: Objectives: Cocoa beans ( Theobroma cacao ) are a highly concentrated source of dietary flavanols that undergo processing steps, to enhance sensory characteristics. Although it is widely accepted that preservation of native cocoa flavanols is critical for retaining bioactivity, it is possible that reactions occurring throughout cocoa processing may generate compounds with novel activities, potentially preserving or enhancing bioactivity. Our objective was to evaluate the impact of fermentation and roasting on levels of flavanols and bioactivity of cocoa. Methods: Combinations of fermentation and roasting parameters were employed via a controlled laboratory fermentation model system and roasting operation. Cocoa powders were produced from unfermented cocoa beans using different treatments representing extremes of fermentation and roasting. Cocoa beans were fermented in a simulated pulp media for 168 h. Fermentation and roasting temperatures varied depending on treatment group. Further processing (winnowing, grinding, pressing) produced cocoa powders for each treatment. Extracts were made from the final beans and powders. Total polyphenols were quantified by the Folin-Ciocalteu assay. HILIC UPLC-MS/MS was employed to analyze flavanols based on their degree of polymerization (DP). Results: Fermentation and roasting contributed to losses of native flavanols. Total polyphenol levels and individual flavanols (DP 1–10) were approximately 27–90% lower in hot fermented/hot roasted cocoa powder and approximately 11–54% lower in cool fermented/cool roasted cocoa powder when compared to the unfermented/unroasted (control) treatment. Hot roasting had the most significant impact on flavanol degradation. There was also a direct relationship between increasing flavanol concentration in cocoa powder and DP. Conclusions: Compared to fermentation, roasting demonstrated a more significant impact on flavanol degradation and composition among cocoa bean treatments. Further research in vitro and in vivo is being performed currently to determine whether these process-induced flavanol losses correlate with reduced anti-obesity and anti-inflammatory activities. Funding Sources: This work was supported by the Agriculture and Food Research Initiative (AFRI) of the US Department of Agriculture.